Studies of Biologically Active Heterocycles: Synthesis, Characterization and Antimicrobial Activity of Some 5-Substitutd-2-Amino-1,3,4-Oxadiazoles - Kumar, Sanjeev (Dhaka University Journal of Pharmaceutical Sciences, 2011)
In the present study, 5-substituted-2-amino-1,3,4-oxadiazoles (4a-k) have been synthesized by the electrochemical oxidation of semicarbazones (3a-k) using platinum anode at room temperature under controlled potential electrolysis in an undivided cell assembly. The structural assignment of these compounds (4a-k) has been made on the basis of elemental analysis, IR, 1H NMR and 13C NMR. The synthesized compounds were screened for their inhibiting activity against Klebsilla penumoniae, Escherichia coli, Bassilus subtilis and Streptococcus aureus and antifungal activity against Aspergillus niger and Crysosporium pannical and results have been compared with the standard antibacterial agents, Streptomycin and antifungal drug, Griseofulvin. The Compounds exhibited significant antibacterial activity and antifungal activity. Key words: Electrochemical oxidation; controlled potential; 5-substituted-2-amino-1,3,4-oxadiazole; semicarbazone; antimicrobial agents DOI: 10.3329/dujps.v9i1.7434 Dhaka Univ. J. Pharm. Sci. 9(1): 53-59 2010 (June)